INOVASI PEMERINTAHAN DESA SUNGAI KALI MELALUI PEMANFAATAN TEKNOLOGI INFORMASI - , Farid Nofiard (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
Latent problems surrounding Human Resources and Information Technology Infrastructure are the main obstacles to the use of Information Technology in the innovation process of the Sungai Kali Village government. The paradigm "asal kawa makan sahari, esok bacari pulang" which was formed among the residents of Sungai Kali Village has also become an obstacle for the Sungai Kali Village government to develop its Village government. However, the Sungai Kali Village government has innovated by utilising information technology through the village website. Although still in the information phase, this innovation is still very likely to be developed to the interaction phase and even to the transformation phase. This research uses descriptive qualitative methods to describe the innovation process carried out by the Sungai Kali Village Government based on Backus's E Government Solution theory.